Existence of an exponential attractor for a p−Kirchhoff model with infinite memory - Noel Figueroa, Pablo Fernando (2022)
The main objective of this work is to study the long-term dynamics of a p−Kirchhoff model with infinite memory exposed to structural forces on a bounded domain Ω ⊂ ℝn. In particular, the existence of a global attractor with exponential attraction rate and finite fractal dimension is shown, that is, the existence of an exponential attractor is proved.